Akad Salam dalam Transaksi Tanah Pemakaman Perspektif Hukum Islam : Studi Desa Donggala Kab Kolaka - Ria Oktaviani; Asni Asni; Musfikah Ilyas (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
This article aims to analyze the implementation of the salam contract in the practice of buying and selling cemetery land in Donggala Village, Kolaka Regency, from an Islamic legal perspective. The focus of this research includes the practice of the salam contract in the sale and purchase of cemetery land, the community's response to the payment system, and its compliance with the provisions of the salam contract in Islamic law. This article uses a qualitative method with a normative sharia and phenomenological approach. Data sources were obtained from adama figures, community leaders, village governments, landowners, and the local community. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The article shows that: (1) The practice of salam contracts in the sale and purchase of burial plots in Donggal Village is carried out with an upfront payment system, but is not accompanied by clarity of location, land boundaries, and written documentation, (2) The public response to this payment system tends to be positive because it provides certainty and peace of mind for families in preparing burial plots, (3) The implementation of salam contracts in these transactions does not fully fulfill the pillars and requirements of salam contracts in Islamic law, especially regarding the clarity of the object of the contract, certainty of the time of use, and recording of the agreement, so that it still has the potential to contain elements of gharar. The implications of this research indicate the need for restructuring the payment system and management of burial plots to align with the principles of justice and welfare in Islamic law. In addition, guidelines for sharia-based burial management are needed as well as socialization regarding contracts and the importance of documenting agreements to protect community rights and prevent future conflicts.